2022
DOI: 10.1111/acem.14546
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive fluids versus standard care in adults with sepsis in the emergency department (REFACED): A multicenter, randomized feasibility trial

Abstract: Background Fluid treatment in sepsis is a challenge and clinical equipoise exists regarding intravenous (IV) volumes. We aimed to determine whether a 24‐h protocol restricting IV fluid was feasible in adult patients with sepsis without shock presenting to the emergency department (ED). Methods The REFACED Sepsis trial is an investigator‐initiated, multicenter, randomized, open‐label, feasibility trial, assigning sepsis patients without shock to 24 h of restrictive, crystal IV fluid administration or standard c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…Additional data and clarifications were provided by the authors of 12 trials. 10 , 11 , 12 , 13 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 …”
Section: Study Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional data and clarifications were provided by the authors of 12 trials. 10 , 11 , 12 , 13 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 …”
Section: Study Design and Methodsmentioning
confidence: 99%
“… 9 Hence, the strategies for IV fluid management in sepsis have been dominated by clinical equipoise. Several RCTs of fluid therapy in sepsis have been published, 10 , 11 , 12 , 13 which substantially increases the quantity of evidence. Therefore, we conducted an updated systematic review with meta-analysis to provide a summary of the available evidence on patient-important outcomes of lower vs higher IV fluid volumes in adult patients with sepsis.…”
mentioning
confidence: 99%
“…Fluids Versus Standard Care in Adults with Sepsis in the Emergency Department (REFACED) trial was recently published that lends support to a future adequately powered trial to detect a between-group mortality difference <5%. 70 Although large-scale randomized investigations have not demonstrated a survival advantage for restricted compared to liberal fluid regimens, there remain concerns regarding excessive fluid administration. These concerns have prompted calls for resuscitation based on precision care for individual patients rather than a simple restricted versus liberal dichotomous breakdown.…”
Section: Pital Another Multicenter Feasibility Study Known As the Res...mentioning
confidence: 99%
“…Similarly, no significant between‐group differences were detected for serious adverse events, days alive without life support, or days alive and out of hospital. Another multicenter feasibility study known as the Restrictive Fluids Versus Standard Care in Adults with Sepsis in the Emergency Department (REFACED) trial was recently published that lends support to a future adequately powered trial to detect a between‐group mortality difference <5% 70 …”
Section: Fluid Therapymentioning
confidence: 99%
“…Similarly, a feasibility study for a trial known by the acronym REFACED Sepsis reported that of the 383 patients screened as eligible, 32% were included and protocol violations occurred in 34% of patients in the restrictive strategy. 31…”
Section: Restrictive Fluid Administrationmentioning
confidence: 99%